Toxicity effects, percent control and cumulative effects of an insecticide on Periplaneta americana - Amante, Elpídio; Barcellos, Deosdedes Francisco; Meneguelli, Carlos Alberto (Pesquisa Agropecuaria Brasileira, 2014)
An experiment using Kepone to control the American Cockroach, Periplaneta americana L., was conducted at Instituto Biológico de São Paulo. Kepone (0.125% decachloro-octahydro 1, 3, 4 methyl - 2 H cyclobutyl - |cd| - pentyl 2 ene) as its active ingredient, was prepared as a bait and as a dough. The association of the bait plus dough and dough alone gave high daily percentage of kill, 14.0% and 13.8% respectively, and the bait treatment alone gave only 4.3% control. The bait treatment plus dough and dough alone gave 70.0% and 69.0% control, respectively, after five days, compared to 21.5% of that in which the chemical was used in bait form.